Cerebral misery perfusion diagnosed using hypercapnic blood-oxygenation-level-dependent contrast functional magnetic resonance imaging: a case report - Gordon, Adam L.; Goode, Stephen; D'Souza, Olympio; Auer, Dorothee P.; Munshi, Sunil K. (Biomed Central, 2010)
Introduction Cerebral misery perfusion represents a failure of cerebral autoregulation. It is animportant differential diagnosis in post-stroke patients presenting with collapses in the presence of haemodynamically significant cerebrovascular stenosis. This is particularly the case when cortical or internal watershed infarcts are present. When this condition occurs, further investigation should be done immediately.